Application of codon usage and context analysis in genes up- or down-regulated in neurodegeneration and cancer to combat comorbidities - Khandia, Rekha; Pandey, Megha Katare; Zaki, Magdi E. A.; Al-Hussain, Sami A.; Baklanov, Igor; Gurjar, Pankaj (Frontiers in Molecular Neuroscience, 2023)
Neurodegeneration and cancers are the disorders presenting inverse co-morbidities due to genes and pathways acting in opposite directions. The study encompassed the study of four genes; three of which (APP, CCND1, CCNE2) were upregulated and one gene (PTPA) was downregulated simultaneously in both disorders. We investigated molecular patterns, codon usage, codon usage bias, nucleotide bias at third codon position preferred codons, preferred codon pair, rare codons, and codon context. Parity analysis revealed the T is preferred over A, and G is preferred over C at third codon position suggestive of no role of composition in nucleotide bias in both the up and downregualyted gene sets, the role of mutational forces is higher in upregulated gene sets than in downregulated ones. The transcript length influences overall %A composition and codon bias and codon AGG influenced most the codon usage in both the upregulated and downregulated gene set. G/C ending codons were preferred for 16 amino acids whereas glutamic acid, aspartic acid, leucine, valine and phenylalanine initiated codon pairs were preferred in all genes. Codons CTA (Leu), GTA (Val), CAA (Gln), and CGT (Arg) were underrepresented in all the gene envisaged. Using the information analyzed in the study may be meticulously used to recode gene. These recoded gene using advanced gene editing tools like CRISPR/Cas or any other gene augmentation technique may be introduced in human body to attain desired and optimum level of gene expression to augment neurodegeneration and cancer simultaneously.